Tajikistan : Poverty Assessment Update - World Bank (Washington, DC, 2012)
The primary purpose of this paper is to update the Poverty Assessment from June, 2000, and to give an assessment of the poverty situation in Tajikistan in 2003 and changes since 1999. The paper is part of an on-going program of work conducted in close cooperation with the Government, based on the Poverty Reduction Strategy Paper and the ongoing work of the PRSP Expert Group. The work program includes the production of a series of relatively short analytical papers rather than one full poverty assessment every four years or so. It is also part of a capacity building process and linked to sector policy dialogue. The paper also aims to use new data to contribute to updating the assessments of the likelihood of meeting the Millennium Development Goals (MDGs).